Sosialisasi Budidaya Tanaman Tarum (Indigofera) Di Lahan Kering Pada Kelompok Tani Bilubahan Desa Tapenpah Kecamatan Insana - Magdalena Sunarty Pareira; Kristina Irnasari Naikofi; Maria Angelina Tuas; Maria Selfiana Pasi (Jurnal Altifani Penelitian dan Pengabdian kepada Masyarakat, 2023)
Tarum (Indigofera ) is a plant that has high commodity value. It can produce a naturally blue color because it contains indican glycosides which are oxidized to indigo (alkaloid compounds). Tarum is included in the Fabaceae family, belonging to a leguminous tree species that has purple flower colors, used as a natural blue dye which is the result of extracting its leaves. This plant is easy to cultivate in dry land because it can improve soil fertility and increase the productivity of dry land. The cultivation of tarum plants is still relatively low, especially on dry land, due to the lack of knowledge of the local community about the potential and methods of cultivating tarum. In addition, tarum can be used as animal feed, tarum leaves are used as forage for animal feed because they contain high protein and nutrients for livestock, and are resistant to drought and disease. This socialization was done in the Bilubahan farmer group in Tapenpah Village, Insana District, North Central Timor Regency. The method used is counseling and the provision of educational materials that are easily accessible to the community of farmer groups, to increase knowledge, and skills and improve productivity and welfare of the community on dry land regarding tarum cultivation. The socialization was attended by the group leader and members of the Bilubahan farmer group, totaling 25 people, this activity went well and smoothly, and the result was that the community was interested and willing to do tarum cultivation. Keywords: Socialization, education, Tarum